PENILAIAN RANAH AFEKTIF PELAJARAN PENDIDIKAN KEWARGANEGARAAN DI KELAS V SDN 06 TAE TUKONG - Bernardus, Bernardus; Mashudi, Mashudi; Mering, Aloysius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aimed to describe the implementation of affective assessment in learning Civic Education in elementary. Implementation of the assessment here includes planning, implementation, and reporting. This research was a qualitative descriptive research. The subject of this research is 1 teacher in Class V at SDN 06 Tae Tukong Subdistrict of Mandor Landak District. Data were collected through interviews and documentation. Technique examination of data validity used was cross check technique. Data analysis technique used inductive analysis technique. The results of this study indicate that: first: the preparation of the assessment plan includes the following activities: (a) the formulation of the objectives of the assessment is done by writing the objectives of the assessment in the plan, (b) the determination of the aspects to be assessed by describing the basic competencies and indicators; (c) The techniques to be used in the affective assessment of observation, interview, and scale, (d) the compilation of assessment instruments are based on the techniques used, (e) the determination of assessment benchmarks using the criterion reference assessment, (f) the frequency of affective judgments has not been maximized. Both assessments include; (a) data collection using three ways, namely interview observation and attitude scale, (b) verification of assessment data is done by separating useful data in affective assessment with useless data, (c) data processing and analysis done by statistic, (d) Interpretation and conclusions are made by converting numeric values into letters and then summarized descriptively, and (e) the follow-up of assessment results by remedial and enrichment. Third reporting of results: (a) the implementation of the report is done by direct and indirect means, and (b) the preparation of the report format there is no standart format. Keywords: Assessment, Affective Range, Civic Education